Portugal : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper of Portugal highlights the discussions on the requirement of policies to overcome structural and cyclical impediments to growth, and secure fiscal consolidation. It analyzes the strength of the company balance sheets in supporting the rebound from recession, and also the links between corporate balance sheet strength and investment. It reviews the challenges in the Portuguese economy, the impact of European Union enlargement on Portuguese trade, the pension prospects, and the implications of various policy reform scenarios.